2010
DOI: 10.1016/j.cub.2010.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Host Defence: Getting By with a Little Help from Our Friends

Abstract: Insects deploy cellular and humoral defences to defend themselves against pathogens and parasites. The recent discovery that fly defences are commonly supplemented by inherited protective microbes suggests that symbiont-mediated protection is common. Resistance evolution may have a more complex dynamic than previously described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…The range of phenotypic effects that viral endosymbionts have on their hosts is poorly understood. For example, to what extent do viral endosymbionts act as mutualists by providing benefits to the host as has been found with bacterial endosymbionts [7]? Viruses have been shown to be capable of such phenotypes [10]; for example, polydnaviruses preventing the larvae of parasitoid wasps from being encapsulated in their host.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The range of phenotypic effects that viral endosymbionts have on their hosts is poorly understood. For example, to what extent do viral endosymbionts act as mutualists by providing benefits to the host as has been found with bacterial endosymbionts [7]? Viruses have been shown to be capable of such phenotypes [10]; for example, polydnaviruses preventing the larvae of parasitoid wasps from being encapsulated in their host.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the pure maternal transmission seen in bacterial endosymbionts does not by itself allow an endosymbiont to spread, as if the infection is at all costly to its host it will lead to a parasite's decline and extinction [51,52]. This has led bacterial endosymbionts to evolve elaborate strategies to enhance their transmission to future generations that range from providing benefits to the host to manipulation of host reproduction-such as causing cytoplasmic incompatibilities between infected and uninfected individuals or distorting the sex ratio towards females [2,5,7].…”
Section: Population Dynamics and The Cost Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike obligate symbionts, they are not essential for successful growth and reproduction and they persist either by manipulating host reproduction for their own benefit [2] or because they confer some fitness advantage on their host. Symbionts have been shown to help their hosts resist abiotic challenges and attack by natural enemies [3][4][5]. The importance of facultative symbionts has become increasingly apparent in the last two decades yet we still know relatively little about how they affect their hosts' interactions in complex food webs.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have reported facultative symbionts that confer protection to their host against parasites and pathogens (Hurst and Hutchence, 2010). Several bacterial symbionts of aphids confer protection against parasitoid wasps (Oliver et al, 2003(Oliver et al, , 2005Vorburger et al, 2009) and fungi (Scarborough et al, 2005;Lukasik et al, 2012).…”
Section: Introductionmentioning
confidence: 99%